Public Disclosures in the Presence of Suppliers and Competitors - Arya, Anil; Mittendorf, Brian; Yoon, Dae‐Hee (Contemporary Accounting Research, 2019)
ABSTRACT Firms’ reluctance at times to publicly disclose financial information is often attributed to concern that the information may be used against them by self‐interested outside parties. These outside parties may interact with the firm in the horizontal realm (e.g., retail competitors) or in the vertical arena (e.g., wholesale suppliers). This article is built on the premise that fully understanding the strategic consequences of disclosure requires joint consideration of horizontal and vertical relationships. When both rivals and suppliers are accounted for, we demonstrate that (i) lower intra‐industry correlation in product demand favors disclosure, with the precise correlation‐cutoff dependent on the firm's use of input suppliers; and (ii) the more a firm relies on input suppliers with pricing power, the less attractive is disclosure.